PERAN POLA ASUH ORANG TUA TERHADAP PERILAKU AGRESIF PADA ANAK - Musslifah, Anniez Rachmawati; Cahyani, Rusnandari Retno; Rifayani, Hastuti; Hastuti, Isnaini Budi (Universitas Sahid Surakarta, 2021)
Children's behavior is influenced by many factors, including parenting patterns and peer groups. One of the patterns of behavior in children that are often encountered in their association with peers is aggressive behavior. The purpose of this study is to determine the role of parenting patterns against aggressive behavior in children. Research using in-depth interview method. Before conducting interviews with participants, researchers conducted a screening to determine participants by giving two questionnaires, namely: The Parenting Styles and Dimensions Questionnaire (PSDQ) to determine the type of parenting patterns and The Aggression Scale: A-Self Report Measure of Aggressive Behavior for Young Adolescents to determine the level of aggressiveness in children. After screening, the researchers selected 3 parents with representatives of each type of parenting pattern to be used as participants in the study. Based on the results of the analysis, foster patterns that have the potential to trigger aggressive behavior in children are authoritarian parenting patterns and permissive parenting patterns.